Pengaruh Reward dan Punishment Terhadap Peningkatan Kinerja Pegawai di Balai Pelestarian Kebudayaan Wilayah XX Maluku - Tupan, Joselina; Laurens, Samson; Selanno, Hendry (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to analyze the influence of reward and punishment on employee performance at the Cultural Heritage Preservation Office, Region XX Maluku. A quantitative approach was used through a survey method involving 93 respondents. Data were analyzed using multiple linear regression to test three main hypotheses: the partial effect of reward on performance, the partial effect of punishment on performance, and the simultaneous effect of both variables on employee performance. The t-test results indicate that both reward and punishment have a significant partial effect on performance, with significance values of < 0.001. Reward contributed 34.6%, while punishment contributed a higher percentage of 60.2%. The F-test results show that reward and punishment simultaneously have a significant impact on employee performance, with an R Square value of 0.838, meaning 83.8% of the performance variance can be explained by these two variables. These findings highlight the importance of implementing appropriate human resource management strategies based on rewards and sanctions to improve employee motivation and productivity. The study recommends enhancing the reward system with more variations and applying fair and consistent punishment as part of performance management policies.